Problems of learning in later Years: Using Agruso Lenses to Explore Adult Learning Experiences at two higher educational Institutions in Bulawayo, Zimbabwe - Zikhali, Whitehead (Advances in Social Sciences Research Journal, 2019)
Whitehead Zikhali, PhD Senior Lecturer: National University of Science and Technology, Institute of Development Studies (NUST-IDS), Bulawayo, Zimbabwe, Cell: +249-901231294 Email-: whitezikhali@gmail.com Abstract Learning is a lifetime experience and engagement. When pursued in formal circles, it is subject to personal (ability, cognition, commitment) and structural (income, class, gender) factors which determine how long a person pursues studies for. Using a modification of Agruso’s gerontological lens, this paper discusses the experiences of students at Bulawayo Polytechnic College and the National University of Science and Technology. The paper stems from a qualitative, exploratory study of two academic groups at NUST Institute of Development Studies spanning over 36 months. It lays out the agenda for an understanding of continuing education not as a challenge which affects older generations but a complex which filters to middle and young adults in developing country contexts. The paper reveals that apart from challenges pertaining to acclimatising to new environments, technologies and processes, formal learning settings offer a raft of challenges for adult learners particularly relating to identity and cognitive aspects. From the challenges discussed, the researcher recommends that (i) continuing education be extended to more sections of society including the informal sector actors (ii) universities be more sensitive to socio-economic group differentials when offering courses for continued adult education. KEYWORDS: adult learning, Agruso, elderly, culture, learning benefits.